2006
DOI: 10.1161/01.atv.0000237569.95046.b9
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine Kinase–Dependent Activation of Endothelial Nitric Oxide Synthase by Angiotensin II

Abstract: Objective-In addition to their role in programmed cell death, cell survival, and cell growth, sphingolipid metabolites such as ceramide, sphingosine, and sphingosine-1-phosphate have vasoactive properties. Besides their occurrence in blood, they can also be formed locally in the vascular wall itself in response to external stimuli. This study was performed to investigate whether vasoactive compounds modulate sphingolipid metabolism in the vascular wall and how this might contribute to the vascular responses. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…6,16 -19 S1P is generated from membrane phospholipids in various cell types, and its production is stimulated by many vasoactive factors, including angiotensin II. 20 In the vasculature, the precise distribution of S1P receptors has still not been clearly established, although S1P1, S1P2, and S1P3 seem to be expressed in vascular cells, with endothelial cells expressing primarily S1P1 and S1P3 and VSMCs expressing S1P1, S1P2, and S1P3. 4 -8,21-26 In the present study, we found that S1P1 and S1P2 but not S1P3 receptors are present in VSMCs from WKYs and SHRSPs.…”
Section: Discussionmentioning
confidence: 99%
“…6,16 -19 S1P is generated from membrane phospholipids in various cell types, and its production is stimulated by many vasoactive factors, including angiotensin II. 20 In the vasculature, the precise distribution of S1P receptors has still not been clearly established, although S1P1, S1P2, and S1P3 seem to be expressed in vascular cells, with endothelial cells expressing primarily S1P1 and S1P3 and VSMCs expressing S1P1, S1P2, and S1P3. 4 -8,21-26 In the present study, we found that S1P1 and S1P2 but not S1P3 receptors are present in VSMCs from WKYs and SHRSPs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, eNOS activation by TNF-α in human endothelial cells was blocked by inhibitors of sphingomyelinase, sphingosine kinase, and blockers of S1P receptors (Mulders et al 2006). This work showed that ERK is another mediator of FTY720P's action on the pump.…”
Section: Fty720p Activates Erkmentioning
confidence: 99%
“…For example, Gschwend et al showed that blockade of AT 1 receptors with angiotensin receptor blockers reversed the increased myogenic constriction observed in HF in rat, 7 suggesting participation of RAS, which has also been linked directly (and indirectly via NADPH oxidase-derived ROS 48 ) to Sphk-dependent vasomotor effects in isolated vessel preparations from nondiseased animals 20,49 and to p38 MAPK activation in VSMCs. 48 Further studies will be needed to dissect the precise contributions of RAS, other neurohormones, or even cytokines implicated in HF such as tumor necrosis factor-␣, 50 to Sphk activity, 51,52 S1P receptor expression, 52 and myogenic responses.…”
Section: Hoefer Et Al S1p Regulates Myogenic Tone In Heart Failure 929mentioning
confidence: 99%